Expert meeting in Rome dedicated to the problems of obstetrics and reproduction - Renzo, Gian Carlo di (REPRODUCTIVE ENDOCRINOLOGY, 2013)
In October 2012 in Rome was held a Congress of the International Federation of Gynecology and Obstetrics (FIGO), in which the expert meeting held in parallel of experts on the obstetrics and reproductionproblems, the latest data and innovative approaches and tactics of the most topical treatment of pathologies. The expert meeting was attended by leading international obstetricians from around the world (UK, USA, Italy,and Belgium). The present review describes some of the papers devoted to the problem of premature birth and the use of local natural progesterone with a view to their prevention, as well as to reduce neonatal morbidity.